'Ordinary science intelligence': a science-comprehension measure for study of risk and science communication, with notes on evolution and climate change. Issue 8 (3rd August 2017) - Kahan, Dan M.
Abstract : This paper describes the 'ordinary science intelligence' scale (OSI_2.0). Designed for use in the empirical study of risk perception and science communication, OSI_2.0 comprises items intended to measure a latent capacity to recognize and make use of valid scientific evidence in everyday decision-making. The derivation of the items, the relationship of them to the knowledge and skills OSI requires, and the psychometric properties of the scale are examined. Evidence of the external validity of OSI_2.0 is also presented. Finally, the utility of OSI_2.0 is briefly illustrated by its use to assess standard survey items on evolution and global warming: when administered to members of a US general population sample, these items are more convincingly viewed as indicators of one or another latent cultural identity than as indicators of science comprehension.